Tailoring Hydrogel Structures: Investigating the Effects of Multistep Cellulose Defibrillation on Polyvinyl Alcohol Composites - Gabriel Goetten de Lima; Bruno Bernardi Aggio; Alessandra Cristina Pedro; Tielidy A. de M. de Lima; Washington Luiz Esteves Magalhães (Gels, 2024)
Defibrillating cellulose through various grinding steps and incorporating it into hydrogels introduces unique properties that warrant thorough exploration. This study investigates cellulose defibrillation at different steps (15–120) using an ultra-fine friction grinder, blended with high-molecular-weight polyvinyl alcohol (PVA), and crosslinked via freeze–thawing. A critical discovery is the influence of defibrillation on the hydrogel structure, as evidenced by reduced crystallinity, thermal degradation, and the enhanced swelling of PVA chains. Despite an increased elastic modulus of up to 120 steps, the synthesized material maintains remarkable strength under hydrated conditions, holding significant promise in biomaterial applications.